Environmental & architectural phenomenology. Vol. 36, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2025)
Besides “Items of interest,” and “citations received,” this issue of EAP includes book notes on geographer Paul Merriman’s Space (2022); philosopher Timothy D. Mooney’s Merleau-Ponty’s Phenomenology of Perception (2024); theologian Benjamín Valentín’s Touched by This Place (2024); and a reprint of naturalist Paul Krafel’s Shifting (2024). There is also an “in memoriam” section for archeologist and anthropologist Christopher Tilley, who died in London in March 2024. In part, he was known for his highly innovative efforts to use first-person phenomenological method to picture how ancient peoples experienced and understood the landscapes and places in which they found themselves. Longer entries begin with independent researcher Stephen Wood, who introduces the possibilities by which aquatic life may have lived connections to the dialectic of darkness and light via such phenomena as water depth and terrestrial location. Next, Israeli architect Nili Portugali discusses her design efforts to implement the theory of wholeness developed by American architect and architectural theorist Christopher Alexander. Portugali’s real-world focus is her design of an apartment house in Tel Aviv, Israel. She considers how her envisioning and building this structure are grounded in and actualize Alexander’s understanding of making environmental and place wholeness.
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals